Cognitive impairment in diabetes mellitus: an exploratory study - Chaudhary, Sameer (International Journal of Advances in Medicine, 2022)
Background: Present study was conducted to estimate the prevalence and evaluate predictors of cognitive function impairment in patients with type 2 diabetes mellitus. Methods: This prevalence study was conducted over one year at a tertiary care teaching hospital in central India. Known cases of type 2 diabetes mellitus of more than one year of duration of illness were considered eligible. Patients with past history of head injury, seizure episode, stroke, chronic kidney disease, those taking antidepressant/antipsychotic treatment and those with pre-existing dementia were excluded. Mini-mental state examination was employed for estimation of the cognitive function. Clinical history, examination and biochemical findings were also evaluated. Results: In all, total 332 patients with mean age of 61.33±11.33 years were studied. Two hundred patients (60.24%) were below 60 years, and 132 patients (39.76%) were over 60 years of age. Two hundred sixteen patients (65.06%) were males, and 116 (34.96%) were females. The mean duration of diabetes mellitus (DM) was 10.17±4.81 years. The mean MMSE score was 22.69±5.26 and 81 (24.4%) patients were observed to have cognitive impairment. The difference in cognitive function between those below 60 years and above 60 years was statistically significant (p=0.0214). Duration of illness was also a significant factor (p=0.0394). But gender was not observed to affect the cognitive function significantly (p=0.2497). Conclusions: Cognitive impairment is common amongst diabetics and is directly related to age and duration of diabetes amongst them; while gender does not influence the cognitive function amongst diabetics.